In vitro and in vivo interactions of selected nanoparticles with rodent serum proteins and their consequences in biokinetics - Kreyling, Wolfgang G.; Fertsch-Gapp, Stefanie; Schäffler, Martin; Johnston, Blair D.; Haberl, Nadine; Pfeiffer, Christian; Diendorf, Jörg; Schleh, Carsten; Hirn, Stephanie; Semmler-Behnke, Manuela; Epple, Matthias; Parak, Wolfgang J. (Beilstein Journal of Nanotechnology, 2014)
When particles incorporated within a mammalian organism come into contact with body fluids they will bind to soluble proteins or those within cellular membranes forming what is called a protein corona. This binding process is very complex and highly dynamic due to the plethora of proteins with different affinities and fractions in different body fluids and the large variation of compounds and structures of the particle surface. Interestingly, in the case of nanoparticles (NP) this protein corona is well suited to provide a guiding vehicle of translocation within body fluids and across membranes. This NP translocation may subsequently lead to accumulation in various organs and tissues and their respective cell types that are not expected to accumulate such tiny foreign bodies. Because of this unprecedented NP accumulation, potentially adverse biological responses in tissues and cells cannot be neglected a priori but require thorough investigations. Therefore, we studied the interactions and protein binding kinetics of blood serum proteins with a number of engineered NP as a function of their physicochemical properties. Here we show by in vitro incubation tests that the binding capacity of different engineered NP (polystyrene, elemental carbon) for selected serum proteins depends strongly on the NP size and the properties of engineered surface modifications. In the following attempt, we studied systematically the effect of the size (5, 15, 80 nm) of gold spheres (AuNP), surface-modified with the same ionic ligand; as well as 5 nm AuNP with five different surface modifications on the binding to serum proteins by using proteomics analyses. We found that the binding of numerous serum proteins depended strongly on the physicochemical properties of the AuNP. These in vitro results helped us substantially in the interpretation of our numerous in vivo biokinetics studies performed in rodents using the same NP. These had shown that not only the physicochemical properties determined the AuNP translocation from the organ of intake towards blood circulation and subsequent accumulation in secondary organs and tissues but also the the transport across organ membranes depended on the route of AuNP application. Our in vitro protein binding studies support the notion that the observed differences in in vivo biokinetics are mediated by the NP protein corona and its dynamical change during AuNP translocation in fluids and across membranes within the organism.
Keywords: biokinetics; gold nanoparticles; protein corona; protein–nanoparticle conjugate; serum protein binding; surface modification

(untitled) - Monopoli, M. P.; Walczyk, D.; Campbell, A.; Elia, G.; Lynch, I.; Baldelli Bombelli, F.; Dawson, K. A. (J. Am. Chem. Soc., 2011)

(untitled) - Lundqvist, M.; Stigler, J.; Elia, G.; Lynch, I.; Cedervall, T.; Dawson, K. A. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Cedervall, T.; Lynch, I.; Lindman, S.; Berggård, T.; Thulin, E.; Nilsson, H.; Dawson, K. A.; Linse, S. (Proc. Natl. Acad. Sci. U. S. A., 2007)

(untitled) - Kreyling, W. G.; Semmler-Behnke, M.; Takenaka, S.; Möller, W. (Acc. Chem. Res., 2013)

(untitled) - Fertsch-Gapp, S.; Semmler-Behnke, M.; Wenk, A.; Kreyling, W. G. (Inhalation Toxicol., 2011)

(untitled) - Rivera-Gil, P.; Jimenez De Aberasturi, D.; Wulf, V.; Pelaz, B.; Del Pino, P.; Zhao, Y.; De La Fuente, J. M.; Ruiz De Larramendi, I.; Rojo, T.; Liang, X. J.; Parak, W. J. (Acc. Chem. Res., 2013)

(untitled) - Schäffler, M.; Semmler-Behnke, M.; Sarioglu, H.; Takenaka, S.; Wenk, A.; Schleh, C.; Hauck, S. M.; Johnston, B. D.; Kreyling, W. G. (Nanotechnology, 2013)

(untitled) - Sperling, R. A.; Pellegrino, T.; Li, J. K.; Chang, W. H.; Parak, W. J. (Adv. Funct. Mater., 2006)

(untitled) - Caballero-Díaz, E.; Pfeiffer, C.; Kastl, L.; Rivera-Gil, P.; Simonet, B.; Valcárcel, M.; Jiménez-Lamana, J.; Laborda, F.; Parak, W. J. (Part. Part. Syst. Charact., 2013)

(untitled) - Semmler-Behnke, M.; Kreyling, W. G.; Lipka, J.; Fertsch, S.; Wenk, A.; Takenaka, S.; Schmid, G.; Brandau, W. (Small, 2008)

(untitled) - Hirn, S.; Semmler-Behnke, M.; Schleh, C.; Wenk, A.; Lipka, J.; Schäffler, M.; Takenaka, S.; Moller, W.; Schmid, G.; Simon, U.; Kreyling, W. G. (Eur. J. Pharm. Biopharm., 2011)

(untitled) - Schleh, C.; Semmler-Behnke, M.; Lipka, J.; Wenk, A.; Hirn, S.; Schäffler, M.; Schmid, G.; Simon, U.; Kreyling, W. G. (Nanotoxicology, 2012)

(untitled) - Kreyling, W. G.; Hirn, S.; Möller, W.; Schleh, C.; Wenk, A.; Celik, G.; Lipka, J.; Schäffler, M.; Haberl, N.; Johnston, B. D.; Sperling, R.; Schmid, G.; et al. (ACS Nano, 2014)

(untitled) - Lipka, J.; Semmler-Behnke, M.; Sperling, R. A.; Wenk, A.; Takenaka, S.; Schleh, C.; Kissel, T.; Parak, W. J.; Kreyling, W. G. (Biomaterials, 2010)

(untitled) - Schäffler, M.; Sousa, F.; Wenk, A.; Sitia, L.; Hirn, S.; Schleh, C.; Haberl, N.; Violatto, M.; Canovi, M.; Andreozzi, P.; Salmona, M.; Bigini, P.; et al. (Biomaterials, 2014)

(untitled) - Ali, Z.; Abbasi, A. Z.; Zhang, F.; Arosio, P.; Lascialfari, A.; Casula, M. F.; Wenk, A.; Kreyling, W.; Plapper, R.; Seidel, M.; Niessner, R.; Knöll, J.; et al. (J. Anal. Chem., 2011)

(untitled) - Salvati, A.; Pitek, A. S.; Monopoli, M. P.; Prapainop, K.; Bombelli, F. B.; Hristov, D. R.; Kelly, P. M.; Aberg, C.; Mahon, E.; Dawson, K. A. (Nat. Nanotechnol., 2013)

(untitled) - Ragnaill, M. N.; Brown, M.; Ye, D.; Bramini, M.; Callanan, S.; Lynch, I.; Dawson, K. A. (Eur. J. Pharm. Biopharm., 2011)

(untitled) - Brandenberger, C.; Rothen-Rutishauser, B.; Mühlfeld, C.; Schmid, O.; Ferron, G. A.; Maier, K. L.; Gehr, P.; Lenz, A.-G. (Toxicol. Appl. Pharmacol., 2010)

(untitled) - Carlson, C.; Hussain, S. M.; Schrand, A. M.; Braydich-Stolle, L. K.; Hess, K. L.; Jones, R. L.; Schlager, J. J. (J. Phys. Chem. B, 2008)

(untitled) - AshaRani, P. V.; Mun, G. L. K.; Hande, M. P.; Valiyaveettil, S. (ACS Nano, 2009)

(untitled) - Haberl, N.; Hirn, S.; Wenk, A.; Diendorf, J.; Epple, M.; Johnston, B. D.; Krombach, F.; Kreyling, W. G.; Schleh, C. (Beilstein J. Nanotechnol., 2013)

(untitled) - Christensen, F. M.; Johnston, H. J.; Stone, V.; Aitken, R. J.; Hankin, S.; Peters, S.; Aschberger, K. (Nanotoxicology, 2010)

(untitled) - Gaiser, B. K.; Fernandes, T. F.; Jepson, M.; Lead, J. R.; Tyler, C. R.; Stone, V. (Environ. Health (London, U. K.), 2009)

(untitled) - Johnston, H. J.; Hutchison, G.; Christensen, F. M.; Peters, S.; Hankin, S.; Stone, V. (Crit. Rev. Toxicol., 2010)

(untitled) - Kittler, S.; Greulich, C.; Diendorf, J.; Köller, M.; Epple, M. (Chem. Mater., 2010)

(untitled) - Loza, K.; Diendorf, J.; Sengstock, C.; Ruiz-Gonzalez, L.; Gonzalez-Calbet, J. M.; Vallet-Regi, M.; Köller, M.; Epple, M. (J. Mater. Chem. B, 2014)